Youth Overcoming Barriers Through Multiple Adult Mentoring Relationships - Martin, Faraji (2020)
African American youth may face several problems that may hinder their positive growth into adulthood. These individuals may not have adults in their lives who aid in overcoming difficulties that halt positive youth development. Mentoring may provide a young person with an adult or several people that can assist youth with problems and help them find the appropriate solutions to overcome them. Numerous studies have provided research on negative influences on youth development, but authors noted that further research on positive youth development among disadvantaged African American youth is necessary. The current study provides information about informal mentoring and the outcomes described by youth involved in multiple adult mentoring relationships. Opportunities and strategies that arise when multiple informal mentors act as role models in helping youth develop are explored in the research. Vygotsky’s social development theory frames the study and guides the research question to address the experiences of young, African American men and women who were mentored in their youth by multiple informal mentors. A case study approach with 8 participants is utilized for this study, with content analysis of data including interviews, contexts, and artifacts to inform the research. Findings from the analysis identify a number of key informal mentoring activities that may contribute to creating a guide for informal mentoring. This study will impact social change by informing community mentoring programs and community leaders about strategies for informal mentoring of young men and women